2020
DOI: 10.1007/s00264-020-04711-w
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of orthopaedic trauma patients during the 2020 COVID-19 pandemic

Abstract: Purpose The outbreak of the SARS-CoV-2 virus has been associated with reports of increased anxiety, depression and fear among the general population. People with underlying psychiatric disorders are more susceptible to stress than the general population. The purpose of this study was to determine the prevalence of concomitant psychiatric conditions in the orthopaedic trauma population during the COVID-19 pandemic. Methods This retrospective cohort study evaluated orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Reported frequencies of abuse, self-harm, thoughts of suicide, and self-injurious behavior were higher among women, black, Asian and minority ethnic groups, people experiencing socioeconomic disadvantage, unemployment, disability, chronic physical illnesses, mental disorders and COVID-19 diagnosis. Furthermore, a study in the United States found an increased number of orthopedic trauma patients reporting a mental health diagnosis post-quarantine compared to pre-quarantine as well as an increased number of patients reporting interpersonal violence as the reason for their injury ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported frequencies of abuse, self-harm, thoughts of suicide, and self-injurious behavior were higher among women, black, Asian and minority ethnic groups, people experiencing socioeconomic disadvantage, unemployment, disability, chronic physical illnesses, mental disorders and COVID-19 diagnosis. Furthermore, a study in the United States found an increased number of orthopedic trauma patients reporting a mental health diagnosis post-quarantine compared to pre-quarantine as well as an increased number of patients reporting interpersonal violence as the reason for their injury ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our review, difficulties were reported by pregnant women in accessing basic prenatal services during the pandemic due to closure and movement restrictions (35) and a previous report found that stay-at-home orders may contribute to women's vulnerability and considered a risk factor for gender based violence (74). Mobility restrictions can increase domestic violence and in our review a study from the United States found an increase in orthopedic trauma patients reporting interpersonal violence post-lockdown compared with pre-lockdown with an increase in fractures in female patients indicating an increase in gender based violence (47). Additionally, a UN human rights report alluded to rise in gender based and domestic violence due to economic and psychosocial challenges (76).…”
Section: Summary Findings Around Vulnerable Groupsmentioning
confidence: 90%
See 1 more Smart Citation
“…With over half of the world population on some form of lockdown in April 2020, mental health of populations became a growing concern as individuals faced unprecedented levels of established mental health risk factors including social isolation, stress and anticipated economic hardship (Monroe and Simons, 1991; Mazure, 1998; Hammen, 2004; Ahnquist and Wamala, 2011; Matthews et al ., 2016; Herbolsheimer et al ., 2018; Economou et al ., 2019; Brooks et al ., 2020). These risk factors not only disproportionately affect individuals with a history of mental health problems (Hao et al ., 2020; Yao et al ., 2020), high-risk groups such as health care workers (Kang et al ., 2020; Liu et al ., 2020; Lu et al ., 2020), COVID-19 patients and survivors (Zhang et al ., 2020 a ), individuals with pre-existing chronic diseases (Ohliger et al ., 2020; Wang et al ., 2020 b ) or unemployed individuals (Zhang et al ., 2020 b ), but also could trigger the onset of mental disorders in previously healthy populations. Alarming statements by public health experts and the United Nations have expressed the concern that COVID-19 could contribute towards a major global mental health crisis (Galea et al ., 2020; UN, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gerade unter den aktuellen Umständen der COVID-19-Pandemie ist mit einer weiteren Zunahme psychischer Erkrankungen zu rechnen. So berichteten Ohliger und Kollegen von einer höheren Prävalenz psychiatrischer Erkrankungen bei orthopädischen Patienten während der COVID-19-Pandemie (76 von 298 Patienten [26 %] vs. 110 von 255 Patienten [43 %], p < 0,001) im Vergleich zu 2019 in den USA [ 19 ]. Darüber hinaus betonten mehrere Studien ein geringeres psychisches Wohlbefinden in der Allgemeinbevölkerung im Vergleich zur Zeit vor COVID-19 sowie eine erhöhte Symptombelastung bei Patienten mit vorbestehenden psychiatrischen Erkrankungen [ 1 , 33 ].…”
Section: Diskussionunclassified